Nghiên cứu ảnh hưởng của xử lý axit đến đặc tính và khả năng tích trữ hyđro điện hóa của ống nano cacbon - Vỹ, Uông Văn; Quế, Lê Xuân (Vietnam Journal of Chemistry, 2014)
Carbon nanotubes (CNTs) was treated in HNO3 3 M or in HCl 3 M + H2O2 30 %, in 8 hours, temperature 80 °C, and stirring speed 500 r/min. Then the CNTs powder was washed with distilled water to pH = 7, dried at temperature 120 oC within 24 hours. The characteristics of CNTs powders were analyzed by SEM, TGA and BET methods, electrochemical hydrogen storage capacity of the material was studied by galvanostatic technique. The characteristics and electrochemical hydrogen absorption capabilities of material has been improved by acid treatments. Purity of the material increased from 92.34 % to 99.9 % for the samples treated with HCl 3 M + H2O2 30 %. Specific surface area increase about 10 m2/g, the pore volume increase and the average size of pores decrease. The discharge capacity of untreated samples is 143.8 mAh/g, the treated samples with HCl + H2O2 solution has the highest discharge capacity, 258 mAh/g. These materials are able to apply in negative electrode additive in NiMH battery. Keywords: Carbon nanotubes, acid treatment, characteristics, electrochemical hydrogen storage, electrode additive.